The Effect of Applying Semi Fowler Position in Reducing Ineffective Breathing Patterns in Congestive Heart Failure (CHF) Patient at RSUD Porsea, Toba Regency (Case Study Research) - Minar Lenny Situmorang; Parulian Dormaida Gultom; Daniel Silitonga; Rifka Banjarnahor (International Journal of Health Engineering and Technology, 2025)
The inefficiency of heart function in supplying the body's metabolic needs is caused by a heart pump pathology condition known as congestive heart failure (CHF). Common symptoms of heart failure are difficulty in breathing when lying down, thus it is necessary to provide good nursing care to heart failure patients by applying a semi fowler position so that the problem of ineffective breathing patterns. The objective of the study is to overcome ineffective breathing patterns by effectively providing a semi fowler position in patients with Congestive Heart Failure (CHF). The study used a descriptive method with a nursing care case study design including assessment, nursing diagnosis, intervention, implementation and evaluation. Based on the result, the nursing actions during 4 days of treatment is that the effectiveness of the semi fowler position can have an effect on reducing ineffective breathing patterns, namely reduced shortness of breath and breathing becomes stable again.